SYNTHESIS AND CHARACTERIZATION OF LEADFREE PIEZOELECTRIC (K0.5Na0.5) NbO3 PRODUCED WITH IMPROVED CALCINATION TEMPERATURE - Nor Amalina, Ahmad; Dzetty Soraya, Abdul Aziz.; Norni Hidayawati, Mat Daud; Rahim, Noor; Amir Azam, Khan (UTM Press, 2020)
Potassium sodium niobate (KNN) is one of the lead free piezoelectric material that catch the attention of researchers and also those in the industrial field because of its stable piezoelectric responses and environmental friendly composition. The recent development of KNN shows that many methods have been used to synthesize the KNN but the stoichiometric Ka0.5Na0.5NbO3 composition is extremely difficult to consolidate. One of the ways to overcome the problem is to precisely pre-calcine and use milling process for proper homogenization followed by natural sintering process. In this paper, attempt has been made to synthesize the KNN produced at 750 oC calcination temperature. The results of 1060oC sintering temperature for 2 hours show a good composition of KNN with orthorhombic crystal structure where the final sintered pellet can reach to a relative density up to 87.13 %.